MEDIA SOSIAL MENJADI ANCAMAN TERHADAP EKSISTENSI KEHARMONISAN RUMAH TANGGA KELUARGA HINDU (KAJIAN ANTROPOLOGI KESEHATAN) - I Kadek Sukiada (Fakultas Dharma Duta, 2018)
Advances in communication technology can provide ease to interact also entertainment through cyberspace. So the limits of mass communication and interpersonal communication become rather pseudo, the emergence of new ways of communicating to society, through social media. The existence of shifting function of the mobile phone, which initially only serves to send a message or call someone has developed far into a 'laptop' that can be easily taken anywhere. Most people prefer to keep a BB pin compared to storing phone numbers. The impact of these developments, so that it needs an increase in public awareness about the surrounding environment, especially families, because unconsciously or consciously has changed the lifestyle of every family in the community. The family will achieve a degree of harmony if it is not based solely on biological factors, but the aspect of affection must prevail within it as the main pillar of maternal stability. The family organization system must be balanced by maintaining the strap within which is a harmony based on love affair. So with sex, in his view is one of the biological needs of living beings, especially by a two-legged creature, having a nose, a two-handed, walking by standing, having a mind, called a human being.